Migrants and markets perspectives from economics and the other social sciences - Kolb, Holger 1977-; Egbert, Henrik 1967- (IMISCOE research, 2008)
Over the course of their interaction, economics and migration research have treated each other with mutual indifference. When migration research attempted to overstretch its bounds, economics reduced its analytical scope to those areas that originally seemed to belong to the genuine economic sphere. This volume considers eleven case studies that aim to overcome the artificial barrier between the two disciplines by applying the economic method to migratory phenomena, utilizing economic theories in order to explain migratory patterns, and regarding the structure and development of markets as crucial to the shaping of population stocks and the flow of migrants